Wastewater treatment performances of horizontal and vertical subsurface flow constructed wetland systems in tropical climate - Suwasa Kantawanichkul (2018)
The study was carried out in 4 concrete beds: two vertical subsurface flow beds (dimension of 1×1.4 × 0.6 m3) and two horizontal subsurface flow beds (dimension of 0.6 × 2.3 × 0.6 m3) planted with Cyperus alternifolius L. Under the average wastewater temperature of 27°C, the hydraulic loading rates (HLR) were varied from 5 to 20 cm/d in order to obtain the optimum operating conditions and compare the removal efficiency. The wastewater was intermittently fed into the vertical subsurface flow beds (5 minutes on and 55 minutes off), and continuously into the horizontal subsurface flow beds. The maximum removal efficiencies were found at the lowest hydraulic loading rate for both systems. The horizontal subsurface flow system had a higher removal rate than the vertical subsurface flow system in terms of COD (the removal rates at 5-20 cm/d were 9.6-33.9 g/m2.d). The vertical subsurface flow system showed higher removal efficiency for TKN and NH4++-N, in every hydraulic loading rate and the removal rates for TKN and NH4++-N were 0.4-1.1 g/m2.d, respectively. Furthermore, it was found that the uptake of N by plants in the horizontal flow system was higher than in the vertical flow system for every hydraulic loading rate (HLR) but the loss of N via adsorption/denitrification was higher in the vertical flow system than in the horizontal flow system, at 20 cm/d HLR. The removal rate constants in the horizontal subsurface flow system for COD and NH4+-N were 0.0166 and 0.0188 m/d and 0.0204 and 0.0287 m/d for the vertical subsurface flow system, respectively.